UMP aims for Top 10 in 43rd SUKUM - UMP, PNC (2018)
Kuantan, 7 August – Universiti Malaysia Pahang aims to be in the top 10 standings in this upcoming 43rd SUKUM. UMP will be hosting this year edition of Kejohanan Sukan Staf Antara Universiti Malaysia.